Effectiveness of Implementation of the Motor Vehicle Tax Fines Administrative Sanctions Elimination Program at the Palu Samsat Technical Implementation Unit - Aditya Pratama; Abdul Rivai; Muh. Nawawi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
his study aims to determine the effectiveness of the implementation of the Program for the Elimination of Administrative Sanctions for Motor Vehicle Tax Fines in the Technical Implementation Unit of Samsat Palu. This study uses a method with descriptive qualitative data. The data obtained in this study are from the results of observations, interviews, and documentation. The data analysis methods are Data Collection, Data Condensation, Data Presentation, and Conclusion/Verification Drawn. The results of this study showthat the Effectiveness of the Implementation of the Program for the Elimination of Administrative Sanctions for Motor Vehicle Tax Fines at the Technical Implementation Unit of Samsat Palu has not been carried out effectively, this is due to the lack of achievement of the effectiveness indicators used in this study, based on the Achievement of Objectives indicator seen from the first aspect, namely, the Realization of Tax Revenue Targets has not been effective judging from the achievements of the three-year realization presentation last. Furthermore, based on the Integration indicator, it is seen from the first aspect, namely Coordination. From the results of the study, it is known that from the aspect of coordination internally and externally, it has not been effective. Second, Socialization. As for those related to the implementation of socialization with taxpayers, it has been carried out effectively. Adaptation indicators, seen from the aspect of Tax Collection Apparatus Resources, are inadequate. Second, Tax Collection Facilities, especially those related to the System Application, have not been optimized so that the management of tax revenue data and information has not been effective. Similarly, field operational support facilities have not been available as needed, the Third Tax Collection Mechanism, where it is known that at the time of the Elimination of Motor Vehicle Tax Fines and the exemption of Motor Vehicle Name Return Duty for the management of UPTB Region I Palu tax collection is not optimal because it does not have a Standard Operating Procedure (SOP) set and still uses SOPs as usual as regulated in regulations